Process method for closed-loop circulation of polyester
By using titanium dioxide nanotube catalyst, the polyester depolymerization is efficiently catalyzed and the repolymerization of small molecule monomers is achieved, which solves the problems of high cost of polyester degradation catalysts and cumbersome purification process in the prior art, and achieves efficient chemical recovery and closed-loop cycle of polyester.
Patent Information
- Application Number
- CN202411508608.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing catalysts for polyester degradation are costly, cumbersome purification process and risk of contaminating products, making it difficult to achieve efficient polyester recycling and closed-loop circulation.
Titanium dioxide nanotubes are used as catalysts and prepared by hydrothermal method, which can efficiently catalyze the depolymerization of polyester and realize the repolymerization of small-molecular monomers, achieving the closed-loop cycle of polyester without the need for additional catalyst.
The efficient chemical recycling and closed-loop cycle of polyester is realized, which reduces the cost of catalysts, simplifies the purification process, avoids the risk of contaminating products, and has high catalyst activity, good selectivity, and is universal.
Smart Images

Figure QLYQS_1 
Figure BDA0005104779140000061 
Figure BDA0005104779140000071
Abstract
Description
[0001] Technical field: The present invention belongs to the field of polyester catalysts, and is a method for preparing a polyester closed-loop catalyst and its application. Background Art
[0002] Waste polyester, especially waste polyethylene terephthalate (PET), has become an important environmental problem facing the world. With the widespread application of polyester fibers, the amount of its waste is also increasing. As the world's largest polyester producer and consumer, China has a considerable annual output of waste polyester, with an annual output of about 20 million tons of domestic waste polyester, and a large amount of waste polyester needs to be imported every year. If these waste polyesters are not effectively treated, they will cause serious pollution to the environment and form "white pollution". The recycling methods of waste polyester mainly include physical methods, chemical methods, namely mechanical recycling methods and chemical depolymerization methods. Mechanical recycling method refers to the regenerated PET obtained by direct blending, melt blending, extrusion granulation and other simple physical and mechanical treatment of waste PET materials. A more promising method is chemical recycling by depolymerization. However, current chemical strategies such as hydrolysis, methanolysis and glycolysis are not cost-effective compared with hydrogenolysis.
[0003] The team of D. Milstein and J. Robertson used a homogeneous catalyst with hydrogen molecules to catalyze the depolymerization of polyester into alcohol monomers. They proposed a method of catalyzing the decomposition of polymers by hydrogenolysis using ruthenium chelates in the presence of a base, and obtained monomers in high yield. However, the high amount of catalyst, complex solvents, and excessively long reaction times hinder the industrial application of this method. In 2022, Agostinho et al. reported the design of a urea: zinc acetate eutectic solvent (DES) system for a continuous, environmentally friendly, and closed-loop method for recycling PEF into rPEF [Green. Chem. 2022, 24 (8): 3115-3119]. However, this method requires the addition of a large amount of metal catalysts for closed-loop recovery of PEF.
[0004] The existing polyester degradation catalysts have high costs, cumbersome purification processes, and the risk of product contamination after the catalytic reaction is completed. Researchers in this field are in urgent need of providing a polyester recovery and degradation method that can further improve the effect of the polyester recovery process.
[0005] [Beneficial effects of this technology]
[0006] The titanium dioxide nanotube catalyst of the present invention can not only efficiently catalyze the depolymerization of polyester into small molecules to achieve chemical recovery of polyester. At the same time, the small molecular monomers recovered by depolymerization can be catalytically polymerized again to obtain polyester materials, without the need for an external catalyst, and the titanium dioxide nanotubes can efficiently catalyze the closed-loop circulation of polyester. The titanium dioxide nanotube catalyst is a green, low-cost polyester catalyst with the advantages of high activity, good selectivity and universal applicability. DETAILED DESCRIPTION
[0007] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0008] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0009] In the embodiments of the present application:
[0010] Preparation Example 1
[0011] Titanium dioxide precursor: titanium chloride and anhydrous ethanol are mixed, mechanically stirred until uniform to obtain a mixed solution, aged in an oven at a temperature of 70°C for 1 day to form a composite gel, and then 30ml of NaOH with a molar concentration of 10mol / L is added, and stirred for 60-90 minutes until the mixture is uniformly mixed; the mixed solution is transferred to a hydrothermal reactor, the reaction temperature is 130-160°C, the reaction time is 24h, the reactor is opened to decant the upper liquid, and the resulting precipitate is repeatedly washed with deionized water until neutral, and then soaked in 30ml of HNO3 solution with a volume concentration of 0.1mol / L for 30 minutes, the soaking process is accompanied by mechanical stirring, and then the acid solution is filtered off, and then washed with deionized water and anhydrous ethanol respectively until neutral, the product is vacuum dried at a temperature of 60°C for 8h to obtain a titanate powder; the powder material is placed in a crucible, and sintered at a temperature of 400°C for 0.5h-1h under the protection of nitrogen or argon atmosphere to obtain a titanium dioxide precursor. Among them, titanium chloride: anhydrous ethanol = 1:25 (volume ratio)
[0012] Titanium dioxide nanotubes: At room temperature, add titanium dioxide precursor and tetrabutylammonium hydroxide to an aqueous alkaline solution and stir until uniform to obtain a mixed solution. The mixed solution is transferred to a hydrothermal reactor. The reaction temperature is 130-160°C and the reaction time is 24 hours. After opening the reactor and decanting the upper liquid, the resulting precipitate is repeatedly washed with deionized water and anhydrous ethanol until it is neutral. The product is vacuum dried at 60°C for 8 hours to obtain titanium dioxide nanotube powder; wherein, titanium dioxide precursor: ammonium hydroxide = 1:8 (molar ratio).
[0013] Preparation Example 2
[0014] Titanium dioxide precursor: titanium chloride and anhydrous ethanol are mixed, mechanically stirred until uniform to obtain a mixed solution, aged in an oven at a temperature of 70°C for 1 day to form a composite gel, and then 30ml of NaOH with a molar concentration of 10mol / L is added, and stirred for 60-90 minutes until the mixture is uniformly mixed; the mixed solution is transferred to a hydrothermal reactor, the reaction temperature is 130-160°C, the reaction time is 24h, the reactor is opened to decant the upper liquid, and the resulting precipitate is repeatedly washed with deionized water until neutral, and then soaked in 30ml of HNO3 solution with a volume concentration of 0.1mol / L for 30 minutes, the soaking process is accompanied by mechanical stirring, and then the acid solution is filtered off, and then washed with deionized water and anhydrous ethanol respectively until neutral, the product is vacuum dried at a temperature of 60°C for 8h to obtain a titanate powder; the powder material is placed in a crucible, and sintered at a temperature of 400°C for 0.5h-1h under the protection of nitrogen or argon atmosphere to obtain a titanium dioxide precursor. Among them, titanium chloride: anhydrous ethanol = 1:25 (volume ratio)
[0015] Titanium dioxide nanotubes: At room temperature, add titanium dioxide precursor and dodecyldimethylbenzylammonium chloride to an aqueous alkaline solution and stir until uniform to obtain a mixed solution. Move the mixed solution to a hydrothermal reactor. The reaction temperature is 130-160°C and the reaction time is 24 hours. After opening the reactor and decanting the upper liquid, the resulting precipitate is repeatedly washed with deionized water and anhydrous ethanol until it is neutral. The product is vacuum dried at 60°C for 8 hours to obtain titanium dioxide nanotube powder; wherein, titanium dioxide precursor: tetrabutylammonium hydroxide = 1:4 (molar ratio).
[0016] Preparation Example 3
[0017] Titanium dioxide precursor: titanium chloride and anhydrous ethanol are mixed, mechanically stirred until uniform to obtain a mixed solution, aged in an oven at a temperature of 70°C for 1 day to form a composite gel, and then 30ml of NaOH with a molar concentration of 10mol / L is added, and stirred for 60-90 minutes until the mixture is uniformly mixed; the mixed solution is transferred to a hydrothermal reactor, the reaction temperature is 130-160°C, the reaction time is 24h, the reactor is opened to decant the upper liquid, and the resulting precipitate is repeatedly washed with deionized water until neutral, and then soaked in 30ml of HNO3 solution with a volume concentration of 0.1mol / L for 30 minutes, the soaking process is accompanied by mechanical stirring, and then the acid solution is filtered off, and then washed with deionized water and anhydrous ethanol respectively until neutral, the product is vacuum dried at a temperature of 60°C for 8h to obtain a titanate powder; the powder material is placed in a crucible, and sintered at a temperature of 400°C for 0.5h-1h under the protection of nitrogen or argon atmosphere to obtain a titanium dioxide precursor. Among them, titanium chloride: anhydrous ethanol = 1:25 (volume ratio)
[0018] Titanium dioxide nanotubes: At room temperature, add titanium dioxide precursor and tetrabutylammonium bromide to an aqueous alkaline solution and stir until uniform to obtain a mixed solution. The mixed solution is transferred to a hydrothermal reactor. The reaction temperature is 130-160°C and the reaction time is 24 hours. After opening the reactor and decanting the upper liquid, the resulting precipitate is repeatedly washed with deionized water and anhydrous ethanol until it is neutral. The product is vacuum dried at 60°C for 8 hours to obtain titanium dioxide nanotube powder; wherein, titanium dioxide precursor: hexabutylammonium hydroxide = 1:8 (molar ratio).
[0019] Example 1
[0020] The titanium dioxide nanotube catalyst synthesized in Preparation Example 1 and 0.1 mol of polyester PET were added to a pressure vessel and mixed. The amount of catalyst was 0.02% mol of the polyester. The pressure vessel was replaced with N2 for 3-5 times, and then the pressure vessel was connected to H2. After that, the pressure bottle was heated without stirring. Under solvent-free conditions, the reaction was carried out at 260°C and 0.1 MPa for 12 hours. The product obtained by depolymerization of PET gradually sublimated from the bottom and crystallized on the inner wall of the bottle. After the reaction, the pressure bottle was cooled to room temperature, and a certain amount of DMSO was added to the bottle. The product 1 obtained by depolymerization was characterized and analyzed by nuclear magnetic resonance and mass spectrometry. The product 1 and its purity are shown in Table 1.
[0021] The depolymerization product 1 was polymerized again without adding an external catalyst. The esterification reaction was carried out under nitrogen protection. The esterification was carried out at 180°C-240°C for 5 hours. The polycondensation reaction was stopped at 260°C for 2 hours. The obtained polycondensation product rPET1. The obtained product was tested for color and viscosity. The results are shown in Table 1.
[0022] Example 2
[0023] The titanium dioxide nanotube catalyst synthesized in Preparation Example 2 and 0.1 mol of polyester PET were added to a pressure vessel and mixed. The amount of catalyst was 0.02% mol of the polyester. The pressure vessel was replaced with N2 for 3-5 times, and then the pressure vessel was connected to H2. After that, the pressure bottle was heated without stirring. Under solvent-free conditions, the reaction was carried out at 260°C and 0.1 MPa for 12 hours. The product obtained by depolymerization of PET gradually sublimated from the bottom and crystallized on the inner wall of the bottle. After the reaction, the pressure bottle was cooled to room temperature, and a certain amount of DMSO was added to the bottle. The product 2 obtained by depolymerization was characterized and analyzed by nuclear magnetic resonance and mass spectrometry. The product 2 and its purity are shown in Table 1.
[0024] The depolymerization product 2 was polymerized again without adding an external catalyst. The esterification reaction was carried out under nitrogen protection. The esterification was carried out at 180°C-240°C for 5 hours. The polycondensation reaction was stopped at 260°C for 2 hours. The obtained polycondensation product rPET2. was tested for color and viscosity. The results are shown in Table 1.
[0025] Example 3
[0026] The titanium dioxide nanotube catalyst synthesized in Preparation Example 3 and 0.1 mol of polyester PET were added to a pressure vessel and mixed. The amount of catalyst was 0.02% mol of the polyester. The pressure vessel was replaced with N2 for 3-5 times, and then the pressure vessel was connected to H2. After that, the pressure bottle was heated without stirring. Under solvent-free conditions, the reaction was carried out at 260°C and 0.1 MPa for 12 hours. The product obtained by depolymerization of PET gradually sublimated from the bottom and crystallized on the inner wall of the bottle. After the reaction, the pressure bottle was cooled to room temperature, and a certain amount of DMSO was added to the bottle. The product 3 obtained by depolymerization was characterized and analyzed by nuclear magnetic resonance and mass spectrometry. The product 3 and its purity are shown in Table 1.
[0027] The depolymerization product 3 was polymerized again without adding an external catalyst. The esterification reaction was carried out under nitrogen protection. The esterification reaction was carried out at 180°C-240°C for 5 hours. The polycondensation reaction was stopped at 260°C for 2 hours. The obtained polycondensation product rPET3. was tested for color and viscosity. The results are shown in Table 1.
[0028] Example 4
[0029] The titanium dioxide nanotube catalyst synthesized in Preparation Example 1 and 0.1 mol of polyester PEF were added to a pressure vessel and mixed. The amount of catalyst was 0.01% mol of the polyester. The pressure vessel was replaced with N2 for 3-5 times, and then the pressure vessel was connected to H2. After that, the pressure bottle was heated without stirring. Under solvent-free conditions, the reaction was carried out at 220°C and 0.1 MPa for 12 hours. The product obtained by depolymerization of PEF gradually sublimated from the bottom and crystallized on the inner wall of the bottle. After the reaction, the pressure bottle was cooled to room temperature, and a certain amount of DMSO was added to the bottle. The product 4 obtained by depolymerization was characterized and analyzed by nuclear magnetic resonance and mass spectrometry. The product 4 and its purity are shown in Table 1.
[0030] The depolymerization product 4 was polymerized again without adding an external catalyst. The esterification reaction was carried out under nitrogen protection at 180°C-210°C for 2h. The condensation reaction was stopped at 230°C for 2h. The condensation product rPEF1. was obtained. The color and viscosity of the obtained product were tested. The results are shown in Table 1.
[0031] Example 5
[0032] The titanium dioxide nanotube catalyst synthesized in Preparation Example 1 and 0.1 mol of polyester PET were added to a pressure vessel and mixed. The amount of catalyst was 0.02% mol of the polyester. The pressure vessel was replaced with N2 for 3-5 times, and then the pressure vessel was connected to H2. After that, the pressure bottle was heated without stirring. Under solvent-free conditions, the reaction was carried out at 260°C and 1MPa for 0.5h. The product obtained by depolymerization of PET gradually sublimated from the bottom and crystallized on the inner wall of the bottle. After the reaction, the pressure bottle was cooled to room temperature, and a certain amount of DMSO was added to the bottle. The product 5 obtained by depolymerization was characterized and analyzed by nuclear magnetic resonance and mass spectrometry. The product 55 and its purity are shown in Table 1.
[0033] The depolymerization product 5 was polymerized again without adding an external catalyst. The esterification reaction was carried out under nitrogen protection. The esterification was carried out at 180°C-240°C for 5 hours. The polycondensation reaction was stopped at 260°C for 2 hours. The obtained polycondensation product rPET4. was tested for color and viscosity. The results are shown in Table 1.
[0034] Example 6
[0035] The titanium dioxide nanotube catalyst synthesized in Preparation Example 1 and 0.1 mol of polyester PET were added to a pressure vessel and mixed. The amount of catalyst was 0.02% mol of the polyester. The pressure vessel was replaced with N2 for 3-5 times, and then the pressure vessel was connected to H2. After that, the pressure bottle was heated without stirring. Under solvent-free conditions, the reaction was carried out at 150°C and 2MPa for 30 hours. The product obtained by depolymerization of PET gradually sublimated from the bottom and crystallized on the inner wall of the bottle. After the reaction, the pressure bottle was cooled to room temperature, and a certain amount of DMSO was added to the bottle. The product 6 obtained by depolymerization was characterized and analyzed by nuclear magnetic resonance and mass spectrometry. The product 6 and its purity are shown in Table 1.
[0036] The depolymerization product 6 was polymerized again without adding an external catalyst. The esterification reaction was carried out under nitrogen protection. The esterification was carried out at 180°C-240°C for 5 hours. The polycondensation reaction was stopped at 260°C for 2 hours. The obtained polycondensation product rPET5. was tested for color and viscosity. The results are shown in Table 1.
[0037] Comparative Example 1
[0038] Tetrabutyl titanate and 0.1 mol of polyester PET were added to a pressure autoclave for mixing. The amount of catalyst was 0.02% mol of the polyester. The pressure autoclave was replaced with N2 for 3-5 times, and then the pressure autoclave was connected to H2. After that, the pressure bottle was heated without stirring. Under solvent-free conditions, the reaction was carried out at 260°C and 0.1 MPa for 12 hours. The pressure bottle was cooled to room temperature, and a certain amount of DMSO was added to the bottle. The product D1 obtained by depolymerization was characterized and analyzed by nuclear magnetic resonance and mass spectrometry. The product D1 and its purity are shown in Table 1.
[0039] Since the traditional polyester catalyst tetrabutyl titanate cannot depolymerize polyester PET, no depolymerization product is obtained and the next step of repolymerization cannot be carried out.
[0040] Comparative Example 2
[0041] Titanium dioxide (commercial product) was used as a catalyst, and the catalyst content was 0.02% mol of polyester. 0.1 mol of polyester PET was added to a pressure autoclave, and the pressure autoclave was replaced with N2 for 3-5 times, and then the pressure autoclave was connected to H2. After that, the pressure bottle was heated without stirring. Under solvent-free conditions, the reaction was carried out at 260°C and 0.1 MPa for 12 hours, and the product obtained by depolymerization of PET gradually sublimated from the bottom and crystallized on the inner wall of the bottle. After the reaction, the pressure bottle was cooled to room temperature, and a certain amount of DMSO was added to the bottle. The product D2 obtained by depolymerization was characterized and analyzed by nuclear magnetic resonance and mass spectrometry. The product D2 and its purity are shown in Table 1.
[0042] The depolymerization product D2 was polymerized again without adding an external catalyst, and the esterification reaction was carried out under nitrogen protection, at 180°C-240°C for 5h, and at 260°C for 2h, but the target product was not obtained. Since the purity of the product obtained by depolymerization was very low and the purity of the monomer did not reach the polymerization level, repolymerization could not be achieved.
[0043] Table 1
[0044]
[0045]
[0046] Note:
[0047] TPA – terephthalic acid;
[0048] MMT – monomethyl terephthalate;
[0049] FDCA – 2,5-furandicarboxylic acid;
[0050] MF – methyl furoate;
[0051] PET – Polyethylene terephthalate;
[0052] PEF——Polyethylene 2,5-furandicarboxylate. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Attached Figure 1 Schematic diagram of the mass spectrum of rPEF product 4.
Claims
1. A polyester closed-loop circulation process, characterized in that: Polyester depolymerizes and repolymerizes under the action of catalyst; The polyester is selected from the group consisting of: Wherein, R is one or more of methyl, ethyl, propyl, butyl, pentyl, phenyl, furyl, and thienyl, and m is one or more of 1 to 6. The catalyst is a titanium dioxide nanotube catalyst; The titanium dioxide precursor in the titanium dioxide nanotube catalyst is prepared by a sol-gel method, and the alkali treatment method is prepared by adding an alkali solution and a modifier into the precursor.
2. A polyester closed-loop circulation process, characterized in that: The preparation of titanium dioxide nanotube catalyst includes the following steps: Titanium salt and anhydrous ethanol are mixed to form a gel, which is subjected to a hydrothermal reaction in a reactor and then calcined to obtain a titanium dioxide precursor, which is then subjected to a precise alkali treatment process to obtain the titanium dioxide nanotube catalyst.
3. The process according to claim 2, characterized in that: The anion is selected from at least one of nitrate, sulfate, acetate and chloride, wherein Ti can also be selected from organic titanium, preferably, the titanium is selected from tetraisopropyl titanate, butyl titanate, TiCl4, and the anion of the metal salt is preferably selected from nitrate. The modifier is selected from one or a combination of dodecyldimethylbenzylammonium chloride, dialkyldimethylammonium, dodecyldimethylamine oxide, and tetrabutylammonium hydroxide; The alkali in the alkali treatment is selected from any one of potassium hydroxide, sodium hydroxide, barium hydroxide, calcium hydroxide and choline. Optionally, the concentration of the aqueous solution of the alkali is 2 mol / L-15 mol / L.
4. A polyester closed-loop circulation process, characterized in that: Catalytic polyester depolymerization includes the following steps: The titanium dioxide nanotube catalyst according to any one of claims 1 to 3 is contacted with the polyester, and the depolymerization product is a monomer; Preferably, hydrogen is added during the depolymerization reaction; Preferably, the amount of titanium dioxide nanotube catalyst used in the depolymerization stage is 0.01% to 1.0% of the polyester. Preferably, the temperature of the depolymerization stage reaction is 150-260°C; Preferably, the reaction time of the depolymerization stage is 0.5 to 30 hours; Preferably, the pressure during the depolymerization stage reaction is 0.1 MPa to 5 MPa.
5. A polyester closed-loop recycling process, wherein the catalytic depolymerization is characterized in that the catalytic system of the method comprises the titanium dioxide nanotube catalyst as described in any one of claims 1 to 3 and the monomer.
6. A method for preparing a catalyst for closed-loop circulation of polyester and its application, wherein the small molecules obtained by depolymerization of the polyester are polymerized again, and the characteristics are that the steps include: directly esterifying the monomers obtained by depolymerization according to the method of claim 4 and the catalyst to synthesize the polyester again, without adding catalyst; preferably, nitrogen protection is used during the esterification reaction; Preferably, the reaction temperature in the esterification stage is 190-240°C; Preferably, the reaction time of the esterification stage is 1-7h; Preferably, the polycondensation stage reaction is carried out under high vacuum; Preferably, the temperature of the polycondensation stage reaction is 210-270°C; Preferably, the reaction time of the polycondensation stage is 0.5-5h.
Citation Information
Patent Citations
Microwave-assisted synthesis method for titanium dioxide nanotube with high catalytic activity
CN102774881A
Titanium dioxide nanometer catalyst and preparation and application thereof
CN105727919A
Method for preparing regenerated polyester by closed-loop recovery of waste polyester with typical green and low-carbon characteristics
CN114031756A
Bimetal catalyst for efficient photo-thermal synergistic catalytic hydrogenolysis of benzene plastic and preparation method of bimetallic catalyst
CN117772254A
Nanostructured titania catalyst with stabilized acidity and process thereof
US20150087506A1